Burden of hypereosinophilic syndromes in the United States: Patients’ perspective - Jared Silver, MD, PhD; Anna Kovalszki, MD; Mary Jo Strobel; Dan Gratie, PharmD, MS; Amy G. Edgecomb, PharmD, MPH; Cara Schmitt, MS; Waseem Ahmed, BSc, MBA; Arijita Deb, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: Hypereosinophilic syndromes (HES) are rare hematologic disorders characterized by hypereosinophilia and eosinophil-driven organ damage/dysfunction. The HES diagnostic and treatment journey is poorly understood. Objective: We sought to describe the experience and disease burden of HES from a patient perspective. Methods: An online cross-sectional survey was completed by US patients aged 18 years and older with self-reported HES or caregivers (recruited via the American Partnership for Eosinophilic Disorders). Data on symptoms, diagnosis process, treatment, health care resource utilization, quality of life, and support structure were collected. Results: The mean age of the respondents (HES, n = 53; caregiver, n = 1) was 43.6 years (80% White and 57% male). One-quarter (26%) received their HES diagnosis in less than 3 months from first symptoms; 30% waited 3 months to 1 year, 37% 1 to 5 years, and 7% more than 5 years. Almost half of the respondents (n = 26) required hospital care 1 to 3 times in the 12 months before diagnosis. Most common symptoms were fatigue (96%), general discomfort (85%), wheezing (80%), rash (78%), and dry cough (76%). The most burdensome symptoms included leg swelling (100%), sweating (78%), and shortness of breath (64%). Symptoms associated with HES end-organ damage (respiratory and hypercoagulability symptoms) were observed. HES substantially impacted quality of life including work quality/productivity, finances, and relationships. Patients additionally wished for their doctor to show more empathy for their symptom burden, pain, and long-term mental health impacts. Conclusions: People with HES face long diagnostic journeys. The findings in this study highlight the heterogeneous symptoms, challenges, and multifactorial burden they experience, providing a voice for patients with HES and enhancing physician awareness to support improved diagnostics and management.